(untitled) (Medico Legal Update, 2020)
Assessment of passive smoking exposure among adults population in a selected urban community area, Kanchipuram District, Tamil Nadu, India. The objectives are to assess the passive smoking exposure among adults population in a selected urban community area, To associate the passive smoking exposure with demographic variables in selected community area. Purposive sampling technique was used to select 96 samples. The data were collected by using passive smoking exposure scale. The collected data were tabulated and analyzed. Descriptive and inferential statistics were used. The result showed that 51% of passive smoking exposure on adequate knowledge where as 43.75% of passive smoking exposure on moderate knowledge where as 5.2% of passive smoking exposure on inadequate knowledge. P value is S=Significant of gender is p=0.17, educational status is p=0.31, occupation is p=0.95. NS=Non Significant of age is p=0.92,residence is p=0.92.